Identification and Functional Characterization of a Novel Variant in the SEMA3A Gene in a Chinese Family with Kallmann Syndrome - Meng Shu; Huixiao Wu; Shuoshuo Wei; Yingzhou Shi; Zongyue Li; Yiping Cheng; Li Fang; Chao Xu (International Journal of Endocrinology)
Background. Kallmann syndrome (KS) is a rare genetic disease characterized by the reproductive system and olfactory dysplasia due to the defective migration of gonadotropin-releasing hormone (GnRH) neurons. However, this disorder is clinically heterogeneous and the genotype-phenotype relationship has not been determined. Objective. The present study aimed to identify the variant causing KS in a Chinese family and evaluate the functional consequences and phenotypes associated with the novel variant. Methods. A Chinese family with KS was screened for pathogenic variants by whole-exome sequencing (WES). Bioinformatic analysis was performed to predict the consequences of the identified variant. The expression of the mutant protein was examined in vitro. Results. A novel heterozygous variant (NM_006080.2 : c.814G > T) in SEMA3A was identified in the patient and his father, which caused the substitution of aspartic acid with tyrosine in codon 272. It was predicted to result in pathogenic significance with a high damaging score and seriously affect protein structure by bioinformatic analysis. In vitro experiments revealed this variant could significantly decrease the expression of SEMA3A. Furthermore, it may cause the disease by failing to induce the phosphorylation of focal adhesion kinase (FAK) in GnRH neurons. Conclusion. Identification and functional characterization of this novel variant in the SEMA3A gene in a Chinese family with Kallmann syndrome extend the genetic variant spectrum of SEMA3A and provide more data about the heterogeneity of KS, which may provide further insights into the diagnosis of KS and help patients get additional data in genetic counseling and timely treatment.